THE INFLUENCE OF SERVICE QUALITY AND PRICE DISCOUNTS ON CONSUMER LOYALTY IN MAXIM TRANSPORTATION SERVICES IN BENGKULU CITY - Dila Puspita; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
This study was determining the effect price promotion and service quality customer satisfaction online motorcycle taxi services. Population of this study people of Bengkulu city who Maxim application. The number samples obtained 120 respondents using 16 formulas. data analysis method used multiple linear regression. The results study shows that (1) Price no significant effect on Online Motorcycle taxi services Maxim Bengkulu City, (2) Promotion has significant effect on Online Motorcycle taxi services Maxim Bengkulu City, (3) Quality not significantly affect Online Motorcycle taxi services Maxim Bengkulu City, (4) Customer satisfaction no significant effect on online taxi services Maxim Bengkulu City.